2D SnO/In2O3 van der Waals Heterostructure Photodetector Based on Printed Oxide Skin of Liquid Metals. Issue 7 (13th February 2019) - Alsaif, Manal M. Y. A.; Kuriakose, Sruthi; Walia, Sumeet; Syed, Nitu; Jannat, Azmira; Zhang, Bao Yue; Haque, Farjana; Mohiuddin, Md; Alkathiri, Turki; Pillai, Naresh; Daeneke, Torben; Ou, Jian Zhen; et al.
Abstract: Heterostructures assembled from atomically thin materials have led to a new paradigm in the development of the next‐generation high‐performing functional devices. However, the construction of the ultrathin van der Waals (vdW) heterostructures is challenging and/or limited to materials with layered crystal structures. Herein, liquid metal vdW transfer method is used to construct large area heterostructures of atomically thin metal oxides of p‐SnO/n‐In2 O3 with ease. The heterostructure exhibits both outstanding photodetectivity of 5 × 10 9 Jones and photoresponsivity of 1047 A W −1 with fast response time of ≤1 ms under illumination of the 280 nm light. Such excellent performances are due to the formation of the narrow bandgap of the staggered gap at the p–n junction produced by the high‐quality SnO/In2 O3 heterostructure. The facile production of high‐quality vdW heterostructures using the liquid metal–based method therefore provides a promising pathway for realizing future optoelectronic devices. Abstract : This work illustrates a framework for the development of van der Waals (vdW) heterostructures using atomically thin surface oxides of the low melting point liquid metals. vdW heterostructures that are made from printing surface oxides of liquid indium (In2 O3 ) and tin (SnO) on top of each other have efficient and fast response features for photodetection.